Modulatory Effects of Probiotics During Pathogenic Infections With Emphasis on Immune Regulation - Raheem, Abdul; Liang, Lin; Zhang, Guangzhi; Cui, Shangjin (Frontiers in Immunology, 2021)
In order to inhibit pathogenic complications and to enhance animal and poultry growth, antibiotics have been extensively used for many years. Antibiotics applications not only affect target pathogens but also intestinal beneficially microbes, inducing long-lasting changes in intestinal microbiota associated with diseases. The application of antibiotics also has many other side effects like, intestinal barrier dysfunction, antibiotics residues in foodstuffs, nephropathy, allergy, bone marrow toxicity, mutagenicity, reproductive disorders, hepatotoxicity carcinogenicity, and antibiotic-resistant bacteria, which greatly compromise the efficacy of antibiotics. Thus, the development of new antibiotics is necessary, while the search for antibiotic alternatives continues. Probiotics are considered the ideal antibiotic substitute; in recent years, probiotic research concerning their application during pathogenic infections in humans, aquaculture, poultry, and livestock industry, with emphasis on modulating the immune system of the host, has been attracting considerable interest. Hence, the adverse effects of antibiotics and remedial effects of probiotics during infectious diseases have become central points of focus among researchers. Probiotics are live microorganisms, and when given in adequate quantities, confer good health effects to the host through different mechanisms. Among them, the regulation of host immune response during pathogenic infections is one of the most important mechanisms. A number of studies have investigated different aspects of probiotics. In this review, we mainly summarize recent discoveries and discuss two important aspects: (1) the application of probiotics during pathogenic infections; and (2) their modulatory effects on the immune response of the host during infectious and non-infectious diseases.